Experience in organization of hydrological and climatic observations at small model catchments of West Siberia - Sergey Gennadievich Kopysov; Roman Valerievich Yarlykov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The relevance of the work is due to insufficient observational data on small watercourses required for climate change monitoring, dangerous hydrological phenomena forecast, culvert installations calculation and efficient exploitation of micro-hydro power plants. The main aim of the study: to justify the choice of optimum methods of automated water runoff accounting and hydrological and climate information collecting for modeling the dynamics of water-balance elements, as well as, to ensure an adaptive land management and the needs of hydrological and geochemical monitoring. The methods used in the study. Of all the elements of water balance it is the surface water runoff that is most accurately measured, reflecting the current active layer moisture on a small watershed. Instruments (designed and manufactured at the Institute of Monitoring of Climatic and Ecological Systems of SB RAS) for the automatic monitoring of water level, of soil, water and air temperatures were established on three small catchments in the diverse climatic conditions. Model watersheds are located in a zone of oligotrophic swamps of southern taiga, in a zone of frost mound bog of forest tundra and mountain zone of southern taiga. Various methods of hydraulic calculations were used for water runoff account: the first one for free overfall round in section broadcrested weir, the second one for uniform motion in natural channels, the third one for the triangular weir with partial drowned downstream. To determine the surface roughness of a certain water flow the measurements of the flow were performed by means of a hydrometric method (current meter) or a volumetric method for low water discharge. The measurements of a level and other meteorological parameters were carried out with an interval of 1:00 and were saved in the control unit.